Macromol. Mater. Eng. 3/2017. Issue 3 (March 2017) - Deravi, Leila F.; Sinatra, Nina R.; Chantre, Christophe O.; Nesmith, Alexander P.; Yuan, Hongyan; Deravi, Sahm K.; Goss, Josue A.; MacQueen, Luke A.; Badrossamy, Mohammad R.; Gonzalez, Grant M.; Phillips, Michael D.; Parker, Kevin Kit
Abstract : Front Cover: Pull spinning is a new nanofiber manufacturing technique that uses a high‐speed rotating bristle to draw anisotropic nanofibers from a polymer solution. The versatile structure and composition of scaffolds formed using pull spinning enables a wide range of applications, including muscle tissue engineering and textile design. This is reported by Leila F. Deravi, Nina R. Sinatra, Christophe O. Chantre, Alexander P. Nesmith, Hongyan Yuan, Sahm K. Deravi, Josue A. Goss, Luke A. MacQueen, Mohammad R. Badrossamy, Grant M. Gonzalez, Michael D. Phillips, Kevin Kit Parker, article number 1600404.